Maternal obesity is associated with a lipotoxic placental environment - Saben, J.; Lindsey, F.; Zhong, Y.; Thakali, K.; Badger, T.M.; Andres, A.; Gomez-Acevedo, H.; Shankar, K. (Placenta (Eastbourne), 2014)
Maternal obesity is associated with placental lipotoxicity, oxidative stress, and inflammation, where MAPK activity may play a central role. Accordingly, we have previously shown that placenta from obese women have increased activation of MAPK-JNK. Here, we performed RNA-sequencing on term placenta from twenty-two subjects who were dichotomized based on pre-pregnancy BMI into lean (BMI 19–24 kg/m2; n = 12) and obese groups (BMI, 32–43 kg/m2; n = 12). RNA-seq revealed 288 genes to be significantly different in placenta from obese women by ≥1.4-fold. GO analysis identified genes related to lipid metabolism, angiogenesis, hormone activity, and cytokine activity to be altered in placenta from obese women. Indicative of a lipotoxic environment, increased placental lipid and CIDEA protein were associated with decreased AMPK and increased activation of NF-κB (p65) in placenta from obese women. Furthermore, we observed a 25% decrease in total antioxidant capacity and increased nuclear FOXO4 localization in placenta from obese women that was significantly associated with JNK activation, suggesting that maternal obesity may also be associated with increased oxidative stress in placenta. Maternal obesity was also associated with decreased HIF-1α protein expression, suggesting a potential link between increased inflammation/oxidative stress and decreased angiogenic factors. Together, these findings indicate that maternal obesity leads to a lipotoxic placental environment that is associated with decreased regulators of angiogenesis and increased markers of inflammation and oxidative stress.